Chinese English as Foreign Language Teachers’ Self-Efficacy and Motivation as Predictors of Burnout - Song, Meiling (Frontiers in Psychology, 2022)
In contemporary education, educators are a central and focal component of academic structures accountable for education growth. Educators have an effective role in presenting and planning an effective and important academic program. However, they usually experience burnout due to their stressful job that affects the procedure of their teaching. So, considering the variables that help them in mitigating their burnout should be taken into account. The concept such as educator efficacy has recently attracted significant attention in education fields which by itself emphasizes educators and gets them into the focus of attention in education. Also, the concept of motivation has a strong relationship with the expert aspect of the educators and its significance for language educators and their students are increasingly gaining respect in various worldwide settings, in which lower educators’ motivation is generally a reason for distress. To focus on the predictability role of these constructs on teachers’ burnout, 428 female and male Chinese English as Foreign Language (EFL) teachers from more than 17 cities from nine provinces of China were asked to fill out the three scales, namely, teacher motivation, efficacy, and burnout. The main results of the study, achieved through Pearson Correlation, postulate that the relationships exist among the variables of the study, and by running multiple regression analysis; it is revealed that both variables, namely self-efficacy and motivation were the predictors of teachers’ burnout, while self-efficacy was a better predictor. Regarding the applications, educator training plans can focus more on educator self-efficacy and motivation, because of their proved important role in decreasing educator burnout.